Characteristics of crystallographic changes in tear in different stages of diabetic retinopathy - I.M. Bezkorovayna; D.O. Nakonechnyi; A.O. Bezkorovayna (Ukrainian Society of Ophthalmologists, 2018)
Introduction. Studying the specific crystallographic signs of tear in the development of diabetic retinopathy is of an extraordinary interest in clinical practice. Aim. To study the changes in the crystollografic signs of tear depending on a stage of diabetic retinopathy. Materials and methods. Under our supervision, there were 84 patients (145 eyes) with diabetes mellitus. Patients were divided into three groups according to the classification of diabetic retinopathy by N.V. Pasechnikova and V.O. Naumenko, adopted by the XII-th Ukrainian Congress of Ophthalmologists. Group 1 consisted of 36 patients (58 eyes) with non-proliferative diabetic retinopathy (NPDRP); Group 2 consisted of 25 patients (42 eyes) with pre-proliferative diabetic retinopathy (PPDRP); Group 3 consisted of 23 patients (45 eyes) with proliferative diabetic retinopathy (PDRP). Results. A vast intermediate area and single point inclusions in the amorphous and intermediate areas of the tear facie was noted in 81% of the NPDRP patients (р<0.01); the pathologic crystallization in the amorphous area of the tear facie and a prevalence of large-size crystals and vast intermediate areas was in 74% of the PPDRP patients (р<0.01); and the increased density of crystal arrangement and single brown crystals were in 93% of the PDRP patients (р < 0.01). Conclusions. A relationship was defined between the changes in the tear crystallography type in the patients with PPDRP and PDRP, who had a crystollogram of type 3 and type 4, respectively, (p <0.01). The additional crystallographic sings of tear, the changes in which correspond to different stages of DRP, were also defined.